DURABILITY OF HEAVY CONCRETE USING BOILER SLAGS WITH CIRCULATING FLUIDIZED BED - Bondar, V. O.; Akhmednabiyev, R. R. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The results of studying the influence of boiler ash slags with a circulating fluidized bed on the freeze-thaw resistance of heavy concretes are presented. The following materials were used in the studies: Portland cement PPC 500 N, sand with the fineness modulus Mf =1.05, crushed granite fraction 5-10 mm, boiler ashes with circulating fluidized bed, hyperplasticizer «Fluid Premia-196». The study was performed using mathematical planning of the experiment. It is proved that with the replacement of sand with ashes, the freeze-thaw resistance is somewhat reduced, but the hyperplasticizer compensates the reduction of freeze-thaw resistance by reducing the W/C ratio, resulting in the formation of super-fine pore structure of concrete. Fine pores in the concrete structure compensate the ice formation stress at low ambient temperatures. The optimal cement consumption has been established in terms of freeze-thaw resistance, both at full and partial replacement of sand with ash. It was also determined that the optimum should be considered the consumption of a hyperplasticizer in the amount of 1.2-1.4% of the cement mass.
Keywords: ash and slag; fluidized bed; freeze-thaw resistance; mathematical planning